A Systematic Review of the Orthopaedic Literature on Truncal and Lower Extremity Injuries in Major League Baseball Players. (August 2021) - Swindell, Hasani W.; Coury, Josephine R.; Dantzker, Nicholas; Lopez, Cesar D.; Saltzman, Bryan M.; Trofa, David P.; Ahmad, Christopher S.
Abstract : Background: Orthopaedic injuries in Major League Baseball (MLB) players can have a tremendous impact on player health, longevity, salaries, and time lost from play. Purpose: To summarize all data published between January 1980 and August 2019 on truncal and lower extremity orthopaedic injuries sustained by MLB players. Methods: A literature review of studies examining injuries in MLB was performed using the PubMed and Embase databases. Included studies focused on truncal and lower extremity injuries in professional baseball players. Studies pertaining to nonorthopaedic injuries, and case reports, were excluded. Results: A total of 41 articles met the inclusion criteria and were selected for the final analysis. Articles were divided based on anatomic region of injury: hip and pelvis (16%), thigh (15%), truncal (14%), knee (13%), and ankle (11%). Most studies (83.7%) were level 3 evidence. Most studies obtained data using publicly available internet resources (29.8%) compared with the MLB Health and Injury Tracking System (22.1%). Conclusion: This review provides physicians with a single source of the most current literature regarding truncal and lower extremity orthopaedic injuries in MLB players. Most research was published on hip and pelvic, truncal, and thigh injuries and consisted of level III evidence.